2011
DOI: 10.1002/bip.21531
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the activity space of peptides binding to diverse SH3 domains using principal property descriptors derived from amino acid rotamers

Abstract: Although there were intensive works addressed on multivariate extraction of the informative components from numerous physicochemical parameters of amino acids in isolated state, the various conformational behaviors of amino acids in complicated biological context have long been underappreciated in the field of quantitative structure-activity relationship (QSAR). In this work, the amino acid rotamers, which were derived from statistical survey of protein crystal structures, were used to reproduce the conformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, appreciable systematic error is present in the plots; that is, low-affinity peptides are commonly overestimated whereas high-affinity samples are underestimated by the model (indicated by the small slopes k of the fit lines). This phenomenon has also been observed in previous statistical investigations of hAmph1 SH3 domain-binding peptides [18,19], and can be explained by the fact that some unknown factors, such as the interactions between separate residues in the peptide sequence and the conformational entropy loss during the binding, which were not considered in our method, may contribute marginally to the affinity.…”
Section: Model Developmentmentioning
confidence: 53%
See 1 more Smart Citation
“…Furthermore, appreciable systematic error is present in the plots; that is, low-affinity peptides are commonly overestimated whereas high-affinity samples are underestimated by the model (indicated by the small slopes k of the fit lines). This phenomenon has also been observed in previous statistical investigations of hAmph1 SH3 domain-binding peptides [18,19], and can be explained by the fact that some unknown factors, such as the interactions between separate residues in the peptide sequence and the conformational entropy loss during the binding, which were not considered in our method, may contribute marginally to the affinity.…”
Section: Model Developmentmentioning
confidence: 53%
“…Zhou et al employed divided physicochemical property scores coupled with genetic algorithm-Gaussian processes to perform a comparative study of a panel of culled SH3-binding peptides, and concluded that diverse properties contribute remarkably to the interactions between the hAmph SH3 and its peptide ligands [18]. Very recently, He et al used principal property descriptors derived from amino acid rotamers (PDAR) to statistically predict the binding affinities of over 13,000 peptides to ten types of SH3 domains, and found that the electrostatics, hydrophobicity, and hydrogen bonds at core residue positions contribute significantly to SH3-peptide binding [19].…”
Section: Introductionmentioning
confidence: 97%
“…d ij is the distance between atoms i and j . η is an atomic attribute, which can be assigned with steric, polar, aquatic, and flexible parameters to characterize van der Waals, electrostatic, hydrophobic, and entropic effects in domain‐peptide interaction, respectively; all parameters including charge, size, hydrophobicity, and flexibility for different protein atoms were taken from previous reports . α is an attenuation factor, and, generally speaking, larger α results in stronger attenuation of the distance‐dependent function, thus focusing on local molecular structure, whereas smaller α causes interatomic interaction more sensitive to distance change, thereby largely overlooking the global structural property.…”
Section: Methodsmentioning
confidence: 99%
“…However, SH3 domain generally exhibits a broad specificity and low affinity to these natural partner peptides . For example, we have systematically optimized the peptide ligands of human amphiphysin‐1 SH3 domain with 20 natural amino acid substitutions at different peptide residues by statistical modeling, side‐chain rotamer sampling and virtual mutagenesis analysis, and found that the SH3‐peptide binding improvement is modest or moderate; the statistical modeling method has also been successfully used to study other protein‐peptide binding phenomena . In addition, natural peptides are not good candidates for therapeutic usage because of low bioavailability and high susceptibility to protease degradation …”
Section: Introductionmentioning
confidence: 99%